Effectiveness of modified mattress suture closing technique over conventional lower segment caesarean section closing technique - Singh, C. P.; Pitale, Devdatt Laxman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of this study was to compare the thickness of the scar and relative thinning of the uterine wall following conventional LSCS closing technique versus new closing technique (modified mattress Suture) and any additional surgical procedure in each group. Methods: A total of sixty patients undergoing primary caesarean for obstetric indications and who were willing for the study were included. In 30 patients uterus was closed by conventional double layer technique (the first layer is suturing with absorbable suture in a continuous running fashion. After first layer is complete, a second continuous stitch is used to invert the first layer, inverting stitch may be horizontal or vertical using same suturing material) and in 30 patient uterus was closed by new modified mattress technique. In both groups same suture material (vicryl 1-0) was used. Measurement of the thickness of scar site and corresponding posterior wall thickness was done following 6 months of caesarean section. Results: The possible parameters of better technique i.e., the mean scar thickness is more and relative as well as percentage thinning is less with this new technique of uterine closure although statistically not significant. Conclusions: Modified mattress suture technique is a single step procedure and gives the feel of double layer uterine closure. Hence the time taken, material. Used and the cost involved will be less along with excellent hemostasis.